Studies of photoinduced molecular dynamics using a fast imaging sensor - Slater, C (2013)
Few experimental techniques have found such a diverse range of applications as has ion imaging. The field of chemical dynamics is constantly advancing, and new applications of ion imaging are being realised with increasing frequency. This thesis is concerned with the application of a fast pixelated imaging sensor, the Pixel Imaging Mass Spectrometry (PImMS) camera, to ion imaging applications. The experimental possibilities of such a marriage are exceptionally broad in scope, and this thesis is concerned with the development of a selection of velocity-map imaging applications within the field of photoinduced molecular dynamics. The capabilities of the PImMS camera in three-dimensional and slice imaging applications are investigated, in which the product fragment Newton-sphere is temporally stretched along the time-of-flight axis, and time-resolved slices through the product fragment distribution are acquired. Through experimental results following the photodissociation of ethyl iodide (CH3CH2I) at around 230 nm, the PImMS camera is demonstrated to be capable of recording well-resolved time slices through the product fragment Newton-sphere in a single experiment, without the requirement to time-gate the acquisition. The various multi-hit capabilities of the device represent a unique and significant advantage over alternative technologies. The details of a new experiment that allows the simultaneous imaging of both photoelectrons and photoions on a single detector for each experimental acquisition cycle using pulsed ion extraction are presented. It is demonstrated that it is possible to maintain a high velocity resolution using this approach through the simultaneous imaging of the photoelectrons and photoions that result from the (3 + 2) resonantly enhanced multi-photon ionisation of Br atoms produced following the photodissociation of Br2 at 446.41 nm. Pulsed ion extraction represents a substantial simplification in experimental design over conventional photoelectron-photoion coincidence (PEPICO) imaging spectrometers and is an important step towards performing coincidence experiments using a conventional ion imaging apparatus coupled with a fast imaging detector. The performance of the PImMS camera in this application is investigated, and a new method for the determination of the photofragment detection efficiencies based on a statistical fitting of the coincident photoelectron and photoion data is presented. The PImMS camera is applied to laser-induced Coulomb explosion imaging (CEI) of an axially chiral substituted biphenyl molecule. The multi-hit capabilities of the device allow the concurrent detection of individual 2D momentum images of all ionic fragments resulting from the Coulomb explosion of multiple molecules in each acquisition cycle. Correlations between the recoil directions of the fragment ions are determined through a covariance analysis. In combination with the ability to align the molecules in space prior to the Coulomb explosion event, the experimental results demonstrate that it is possible to extract extensive information pertaining to the parent molecular structure and fragmentation dynamics following strong field ionisation. Preliminary simulations of the Coulomb explosion dynamics suggest that such an approach may hold promise for determining elements of molecular structure on a femtosecond timescale, bringing the concept of the `molecular movie' closer to realisation. Finally, the PImMS camera is applied to the imaging of laser-induced torsional motion of axially chiral biphenyl molecules through femtosecond Coulomb explosion imaging. The target molecules are initially aligned in space using a nanosecond laser pulse, and torsional motion induced using a femtosecond 'kick' pulse. Instantaneous measurements of the dihedral angle of the molecules are inferred from the correlated F+ and Br+ ion trajectories following photoinitiated Coulomb explosion at various time delays after the initial kick pulse. The technique is extended to include a second kick pulse, in order to achieve either an increase in the amplitude of the oscillations or to damp the motion, representing a substantial degree of control of the system. Measurements out to long kick-probe delays (200 ps) reveal that the initially prepared torsional wave packet periodically dephases and rephases, in accordance with the predictions of recent theoretical work.